Genealogy of Mongirdai Nobility - Klietkutė, Jolanta (Bibliotheca Lituana, 2019)
The Author dealswith the forgotten history of the Mongird family of Samogitia. After conductinganalysis of Mongirdai family, genealogical table was compiled. According to statististics, extended family was active in both number of persons and in geographical distribution. Mongird(as) descendantsspread over much of the territory of the Polish–Lithuanian Commonwealth – formally, the Crown of the Kingdom of Poland and the Grand Duchy of Lithuania and, after 1791, the Commonwealth of Poland and Tsar Russia (Russian Empire). Family itself Most members of the extended family bacame of priests, doctors,officers, artists, and public figures. For example, two brothers Vladislovas and Vytautas from a Mongird Mišučiai Manor became well known active participants inthe Lithuanian – Polish Nationalrevival back in 1863–1864. Their cousin patriot Vaclovas, a resident of Vilnius Town, who was fighting in the ranks of Polish Legion, and cousin Jadvyga Mongirdaitė were laid in Vilnius Pameriai Memorial. Their Grandmother Michalina Bankauskaitė was a great supporter of a Revival of 1863–1864. There are some unsolved relations and issues between the names of Mangirdaitis and Mongirdas that have notbeen identified yet. In the other words, Lithuanian genealogists and other researchers stillhave to work diligently (closely) to investigate and revive the history of this old Mongird tribe.